Tissue-on-a-Chip: Microphysiometry With Human 3D Models on Transwell Inserts - Schmidt, Christian; Markus, Jan; Kandarova, Helena; Wiest, Joachim (Frontiers in Bioengineering and Biotechnology, 2020)
Microphysiometry showed to be a useful tool to monitor the energy metabolism of living cells and their interaction with other cells. In the past, the technique was mainly used for monitoring of 2D monolayers of cells. Recently, our group showed that it is possible to monitor the extracellular acidification rate (EAR) and transepithelial electrical resistance (TEER) of 3D skin constructs in an automated assay maintaining an air liquid interface (ALI) with a BioChip which was extended by a rapid prototype printed encapsulation. In this work we present an optimized multi-channel intestine-on-a-chip by monitoring TEER of the MatTek 3D-small intestinal tissue model (EpiIntestinalTM). The experiments are performed for one day during which a 60-minute-long cycle is repeated periodically. Each cycle consists of three parts; first: ALI, second: application of measurement medium / test substance for the TEER measurement and third: rinse cycle. A cytotoxic and barrier disrupting benchmark chemical (0.2 % sodium dodecyl sulfate) was applied after 8 h of initial equilibration. The material caused time-dependent reduction of the TEER which cannot be observed with typical cytotoxicity measurement methods. This work shows a proof-of-principle of a multi-channel, time-resolved TEER monitoring of a 3D intestine model maintaining an automated ALI. Multilayer cell models combined with the IMOLA-IVD technology are a promising research tool for the use in the field of toxicology, cellular metabolism studies or drug absorption research.